Energy systems, materials and designing in mechanical engineering - Elena, Gurova (Applied mechanics and materials,, 2015)
Collection of selected, peer reviewed papers from the International Conference for Young Scientists "ELECTRICAL ENGINEERING. ELECTROTECHNOLOGY. ENERGY", June 9-12, 2015, Novosibirsk, Russia.